Testing the use of port biological baseline surveys to support relevant marine alien species management applications in Africa - Awad, Alexander Adnan (Department of Biological Sciences, 2019)
The prevention of non-native marine species introductions is the first line of defense in the management of alien invasive species problems occurring on coastlines around the world. Ports and the shipping industry have been targeted as a sector requiring increased attention and regulation to reduce the significance of the ballast water and biofouling pathways. Ballast water management (BWM) processes have matured significantly at international levels over recent decades, with the support of the International Maritime Organization (IMO) and its BWM Convention. The development of baseline species and environmental data for port areas is increasingly recognized as a foundational step in managing ports and ships with respect to potentially harmful species transfers. Several countries have been conducting port biological baseline surveys using protocols developed at the Centre for Research on Introduced Marine Pests (CRIMP) in Australia, which has become the recommended approach at the IMO for developing countries tackling this issue. This study applies the CRIMP methodology for conducting comprehensive baseline surveys in three key African ports to examine the relevance for practical and effective management outcomes. Lessons learned through survey implementation were consolidated into a set of guidelines for conducting port surveys in developing regions. The generation of species and environmental data allowed for investigation of methodologies for shipping-focused risk assessment for new species introductions. Furthermore, the ability of risk assessment processes to support decisions for Port State Control measures related to BWM was tested though the development of a ship-specific decision support system. Where the presence of a potentially problematic species has been recorded, the role of species-specific risk assessment was also considered. The European Green Crab Carcinus maenas, presently found in isolated bays of South Africa was assessed with respect to the validation of management concerns related to the likelihood for further spread and impact, especially to the valuable aquaculture sector.